2022
DOI: 10.3389/fnagi.2022.970263
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative meta-analysis of vitamin C in the pathophysiology of Alzheimer’s disease

Abstract: PurposeAlzheimer’s disease (AD) is a multifaceted neurodegenerative disorder with many complex pathways feeding into its pathogenesis and progression. Vitamin C, an essential dietary antioxidant, is vital for proper neurological development and maintenance. This meta-analysis and systematic review attempted to define the relationship between vitamin C plasma levels and AD while highlighting the importance and involvement of vitamin C in the pathogenesis of AD.Materials and methodsPRISMA guidelines were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…In fact, the brain needs more ascorbate than any other organ 81 . Links of vitC deficiency with brain diseases such as Parkinson's disease 82 and Alzheimer's disease (AD) are known 83–86 . Therefore, our study suggests that understanding the role of placental REST in the maintenance of brain vitC in the postnatal stages is important to investigate the developmental origin of health and disease (DOHaD) of the adult brain 79 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, the brain needs more ascorbate than any other organ 81 . Links of vitC deficiency with brain diseases such as Parkinson's disease 82 and Alzheimer's disease (AD) are known 83–86 . Therefore, our study suggests that understanding the role of placental REST in the maintenance of brain vitC in the postnatal stages is important to investigate the developmental origin of health and disease (DOHaD) of the adult brain 79 …”
Section: Discussionmentioning
confidence: 93%
“…81 Links of vitC deficiency with brain diseases such as Parkinson's disease 82 and Alzheimer's disease (AD) are known. [83][84][85][86] Therefore, our study suggests that understanding the role of placental REST in the maintenance of brain vitC in the postnatal stages is important to investigate the developmental origin of health and disease (DOHaD) of the adult brain. 79 Our findings further show that DNA methylation is impacted in the adult brain due to the loss of placental REST, but in a sex-biased manner.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, serum vitamin C levels offer a more robust assessment of tissue vitamin C, providing valuable insights into its functions in disease prevention [ 28 ]. Numerous studies have underscored the close relationship between serum vitamin C concentration and the risk of various chronic diseases, including heart failure [ 29 ], cancer [ 30 , 31 ], cognitive dysfunction [ 32 ], and Alzheimer’s disease [ 33 ]. A prior study in Japan observed a positive linear correlation between serum vitamin C concentration and eGFR [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the analysis of the co-citation count among the 10 references, most were human experiments, and four were randomized controlled trial (RCTs). The number of citations can be regarded as a relatively reasonable indicator to evaluate the quality of publications, which indicates that vitamins D, E, and B are the focus of current research, but recent research shows that vitamin C supplementation is a feasible strategy for prevention and treatment of AD (Hamid et al, 2022), Vitamin C treatment restored Aβ induced abnormal metabolites, and the role of antioxidants in the repair of AD metabolic disorder provide a new metabonomic observation and explanation (Zhang et al, 2022). Thus, VK2 may also play an important role in the prevention and treatment of AD (Popescu and German, 2021).…”
Section: Discussionmentioning
confidence: 99%